Renal Sodium Handling in Relation to Environmental and Genetic Factors in Untreated Chinese. (1st October 2020) - Kang, Yuan-Yuan; Cheng, Yi-Bang; Guo, Qian-Hui; Sheng, Chang-Sheng; Huang, Qi-Fang; Xu, Ting-Yan; Li, Yan; Wang, Ji-Guang
Abstract: BACKGROUND: We investigated proximal and distal renal tubular sodium handling, as assessed by fractional excretion of lithium (FELi ) and fractional distal reabsorption rate of sodium (FDRNa ), in relation to environmental and genetic factors in untreated patients. METHODS: Our study participants were suspected hypertensive patients being off antihypertensive medication for ≥2 weeks and referred for 24-hour ambulatory blood pressure monitoring. We collected serum and 24-hour urine for measurement of sodium, creatinine, and lithium concentration, and calculated FELi and FDRNa . We genotyped 19 single-nucleotide polymorphisms associated with renal sodium handling or blood pressure using the ABI SNapShot method. RESULTS: The 1, 409 participants (664 men, 47.1%) had a mean (±SD) age of 51.0 ± 10.5 years. After adjustment for host factors, both FELi and FDRNa were significantly ( P ≤ 0.01) associated with season and humidity, explaining ~1.3% and ~3.5% of the variance, respectively. FELi was highest in autumn and lowest in summer and intermediate in spring and winter ( P = 0.007). FDRNa was also highest in autumn but lowest in winter and intermediate in spring and summer ( P < 0.001). Neither FELi nor FDRNa was associated with outdoor temperature or atmospheric pressure ( P ≥ 0.13). After adjustment for host and environmental factors and Bonferroni multiple testing, among the 19 studied genetic variants, only rs12513375 was significantly associated with FELi and FDRNa ( P ≤ 0.004) and explained about 1.7% of the variance. CONCLUSIONS: Renal sodium handling as measured by endogenous lithium clearance was sensitive to major environmental and genetic factors. Our finding is toward the use of these indexes for the definition of renal tubular dysfunction.